A Review on Sound Absorption Properties Using Natural Fibers - Mahadzir, Muhammad Alimshah; Abu Bakar, Hasniza (Recent Trends in Civil Engineering and Built Environment, 2021)
Research on the sound absorbing material is currently giving a pleasing environment. Thus, the choice of material for sound absorbing material is the priority.  Based on the point of view of environmental protection, a new acoustic material was created. There are fewer reports on natural fibers usage that focus on the material as sound absorbing material using the different method in determination of coefficient. This research is carried out to identify type of natural fibers as a panel of sound absorption and to determine the performance of natural fibers through physical and mechanical properties. The determination of natural fibers as a panel of sound absorption are from reviewing from the previous research. Based on the list of natural fibers, the performance of natural fibers are compared through physical and mechanical properties using an analysis graph from Microsoft Excel. For the conclusion, the physical and mechanical properties also affect the properties of natural fibers and all the panels can be consider as good absorptive materials. Overall results showed that all the natural fibers are promises to be as one of the major requirements for human comfort today for sound absorption quality. The use of these materials as a sound insulation product provides effective solutions for waste management problems.